Posttranslational Modifications of FERREDOXIN-NADP(+) OXIDOREDUCTASE in Arabidopsis Chloroplasts - Lehtimäki, Nina (Plant Physiol, 2014)
Rapid responses of chloroplast metabolism and adjustments to photosynthetic machinery are of utmost importance for plants’ survival in a fluctuating environment. These changes may be achieved through posttranslational modifications of proteins, which are known to affect the activity, interactions, and localization of proteins. Recent studies have accumulated evidence about the crucial role of a multitude of modifications, including acetylation, methylation, and glycosylation, in the regulation of chloroplast proteins. Both of the Arabidopsis (Arabidopsis thaliana) leaf-type FERREDOXIN-NADP(+) OXIDOREDUCTASE (FNR) isoforms, the key enzymes linking the light reactions of photosynthesis to carbon assimilation, exist as two distinct forms with different isoelectric points. We show that both AtFNR isoforms contain multiple alternative amino termini and undergo light-responsive addition of an acetyl group to the α-amino group of the amino-terminal amino acid of proteins, which causes the change in isoelectric point. Both isoforms were also found to contain acetylation of a conserved lysine residue near the active site, while no evidence for in vivo phosphorylation or glycosylation was detected. The dynamic, multilayer regulation of AtFNR exemplifies the complex regulatory network systems controlling chloroplast proteins by a range of posttranslational modifications, which continues to emerge as a novel area within photosynthesis research.